2017
DOI: 10.1007/s00595-017-1551-5
|View full text |Cite
|
Sign up to set email alerts
|

The surgical outcomes of lung cancer combined with interstitial pneumonia: a single-institution report

Abstract: Patients with lung cancer and IIP have a higher risk of chest surgery and a poor prognosis. Very careful surgery and perioperative management are needed, because AEs are often difficult to AE predict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Furthermore, AE-IP developed in 5 (3.3%) of 151 patients after pulmonary surgery in our study. This figure is similarly lower than that in previous studies (9.5–22.5%) [612] and also lower than in our previous study (8.5%) that was conducted at the same hospital as the present study [20]. We believe that this difference in frequency of AE-IP reflects differences in patient selection.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, AE-IP developed in 5 (3.3%) of 151 patients after pulmonary surgery in our study. This figure is similarly lower than that in previous studies (9.5–22.5%) [612] and also lower than in our previous study (8.5%) that was conducted at the same hospital as the present study [20]. We believe that this difference in frequency of AE-IP reflects differences in patient selection.…”
Section: Discussioncontrasting
confidence: 72%
“…Maniwa T et al did not found a significant correlation between blood loss and ILD ( 20 ). However, Taniguchi et al indicated that the blood loss in ILD patients suffering from acute exacerbation postoperation was greater than that in ILD patients without AE (628±338.7 vs. 272.2±451.7 mL, P=0.024) ( 21 ). We believed that combined with ILD would increase the difficulty of surgery, increase the operation time and blood loss, and might cause postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies that examined the survival of patients with IP after undergoing NSCLC resection [ 4 , 5 , 15 - 17 ], they examined the prognostic roles of clinicopathological factors, including Krebs von den Lungen-6 (KL-6), but not tumor markers. Therefore, in the present study, we examined the prognostic significance of serum tumor markers, and found that serum CEA level might serve as an efficient prognostic indicator after surgery in NSCLC with IP.…”
Section: Discussionmentioning
confidence: 99%